2022
DOI: 10.1590/0102-672020220002e1670
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Chronic Pain After Laparoscopic Inguinal Hernia Repair Using the Transabdominal Technique Comparing With Fixation of the Mesh With Staples, With Glue or Without Fixation? A Clinical Randomized, Double-Blind Trial

Abstract: BACKGROUND: Regarding postoperative pain, it remains unclear whether non-fixation of the polypropylene prosthesis in transabdominal preperitoneal inguinal hernia repair produces the same outcomes as mesh fixation with glue or tackers. In addition, hernia recurrence is another aspect to be assessed in the comparison between non-fixation and mesh-fixation techniques (tackers and glue). AIMS: This study aimed to evaluate the incidence, quality of pain, and recurrence in patients undergoing laparoscopic inguinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Early and chronic pain are elements of interest to evaluate the effects of different mesh fixation techniques. All the chosen papers analysed these aspects, but in particular 3 reported data related to early pain in OS [ 31 , 34 , 35 ] and 4 related to early pain in LS [ 31 , 43 , 44 , 46 ], 8 studies reported data related to chronic pain in OS [ 21 , [31] , [32] , [33] , [35] , [36] , [37] , 45 ] and 5 reported data on chronic pain in LS [ 25 , 31 , 39 , 43 , 46 ]. Patients were asked to record pain scores 12 or 24 h after the surgical procedure using the VAS index.…”
Section: Resultsmentioning
confidence: 99%
“…Early and chronic pain are elements of interest to evaluate the effects of different mesh fixation techniques. All the chosen papers analysed these aspects, but in particular 3 reported data related to early pain in OS [ 31 , 34 , 35 ] and 4 related to early pain in LS [ 31 , 43 , 44 , 46 ], 8 studies reported data related to chronic pain in OS [ 21 , [31] , [32] , [33] , [35] , [36] , [37] , 45 ] and 5 reported data on chronic pain in LS [ 25 , 31 , 39 , 43 , 46 ]. Patients were asked to record pain scores 12 or 24 h after the surgical procedure using the VAS index.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for exclusion are outlined in Figures 1, 4. Subsequently, four additional studies (15, 19,33,34) were incorporated into the synthesis, along with 16 studies from previous meta-analyses (17,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), particularly the one conducted by Nan Hu et al (20). In total, this metaanalysis included a total of 20 articles (15, 17,19,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Subsequently, four additional studies (15, 19,33,34) were incorporated into the synthesis, along with 16 studies from previous meta-analyses (17,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), particularly the one conducted by Nan Hu et al (20). In total, this metaanalysis included a total of 20 articles (15, 17,19,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The collective sample involves 2,928 patients with inguinal hernias, distributed as 1,582 in the TMF group and 1,346 in the GMF group, meeting the inclusion and exclusion criteria.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, the techniques for keeping mesh in place can be categorized as no mesh fixation and mesh fixation. No mesh fixation is the method used for laparoscopic inguinal hernias, as reported both in TEP [18][19][20] and TAPP [21][22][23]. At the end of the surgical procedure, expelling the air allows the peritoneum to attach to the mesh, while intra-abdominal pressure causes the extraperitoneal space to naturally close and constrict, allowing the mesh to be fixed in position.…”
Section: Technique For Keeping Mesh In Placementioning
confidence: 99%